New Structure for Photovoltaic Systems with Maximum Power Point Tracking Ability - Mostafa Barzegar Kalashani; Murtaza Farsadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This paper proposes a new structure for photovoltaic (PV) arrays with a new inverter topology. A quasi-Z-Source DC-DC Converter (qZSC) with capability of dividing its output voltage to the same voltages and tracking maximum power point is proposed. The Proportional-Integral Incremental Conductance (PI-IncCond) method is used for maximum power point tracking (MPPT). Description of proposed structure along with detailed simulation results that verify its feasibility are given to demonstrate the availability of the proposed system by MATLAB/Simulink software.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6365